Additive effects of exposure to silica dust and smoking on pulmonary epithelial permeability: a radioaerosol study with technetium-99m labelled DTPA. Issue 3 (March 1993) - Nery, L E; Florencio, R T; Sandoval, P R; Rodrigues, R T; Alonso, G; Mason, G R
Abstract : BACKGROUND: Increased pulmonary epithelial permeability evaluated by the rate of clearance from lung to blood of the radioaerosol solute technetium-99m labelled diethylenetriamine pentaacetate (99mTc-DTPA) has been reported in smokers and in workers exposed to silica dust. A study was carried out to determine whether there are additive effects of cigarette smoke and exposure to silica dust on clearance rates of 99mTc-DTPA in ceramic workers. METHODS: Thirty one subjects with silicosis were studied, of whom 18 smoked cigarettes and 13 were non-smokers. They had similar histories of exposure to silica dust, and radiological alterations consistent with silicosis. The results from these patients were compared with those from normal subjects and smokers previously studied by the authors. RESULTS: Pulmonary function values were normal in most patients and not significantly different among groups. The median (range) rate of clearance of 99mTc-DTPA in smokers with silicosis was 4.1 (1.9-12.7) %/minute, which was higher than the rates in non-smoking patients with silicosis of 2.2 (1.1-6.6) %/minute and in smokers without exposure to silica dust of 2.9 (1.6-4.5) %/minute. These differences were more evident and significant when the clearance rates of the lower lobes of the three groups were compared. Clearance rates higher than 3%/minute were much more frequent in smokers with silicosis (85%) than in non-smoking patients with silicosis (15%) and in smokers (40%). CONCLUSION: In ceramic workers with radiographic changes resulting from exposure to silica dust, there is an additive effect of inhalation of silica dust and cigarette smoking on clearance rates of 99mTc-DTPA.